European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C M; SCOTT, J K (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C. M.; SCOTT, J. K. (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease